KOMPETENSI KOMUNIKASI PEMASARAN MAMA-MAMA PAPUA PENJUAL NOKEN DALAM MENINGKATKAN TECHNOPRENEURSHIP DI KOTA JAYAPURA - laili, izzatul (Jurnal Common, 2024)
This research analyses marketing communication competencies of the female Naken (traditional Indonesia woven bag native to sellers og papua to increase the technopreneurship in Jayapura. It employs phenomenology methode and takes the female Noken sellers of Papua meeting the criteria such as selling Noken, meeting sosial economic status, and not a member of community such as UMKM (Micro, Small, and Medium-sized Enterprises). The data are collected through in-depth interviews, observation, and documentation study. It is found that the female Noken sellers of Papua understanding of technopreneurship; this the use of digital technology in entrepreneurship is also low. They have no knowledge about how to sell Noken online or via social media platforms such as facebook , Instagram, and whatsapp. In addition, the sell Noken conventionally in front of malls, sidewalk, tradisional market, or roadside because it is considered easier and not complicating. The market communication competencies of the female Noken sellers of Papua is still poor; they sell Noken passively without trying to offer the Noken to the prospects. The seller’ communication with the prospects is unconvincing and limited as there is no bargain whit the buyers. Therefore, the abstacles encountered by the female Noken sellers of Papua in developing the market communication competency in technopreneurship field are that they have same limitations related to ownership og digital gadget such as Cellular Phone, low education background, lack of motivation, and inability to adapt with digital technology. Keywords : Marketing Communication Competency, Technopreneurship, Noken Jayapura